Ответ:
Пошаговое объяснение:
a) lim(x→1) (x²+2x-3)/(x²-5x+4)=(неопределённость 0/0)=
=lim(x→1) (x²+2x-3)'/(x²-5x+4)'=lim(x→1) ((2x+2)/(2x-5)=(2*1+2)/(2*1-5)=-4/3.
б) lim(x→4) (√x-2)/(x-4)=(неопределённость 0/0)=lim(x→4) (√x-2)'/(x-4)'=
= lim(x→4) (1/(2*√x*1)=1/(2*√4)=1/(2*2)=1/4.
в) lim(x→-2/3) (3x²-4x-4)/(3x²-7x-6)=(неопределённость 0/0)=
=lim(x→-2/3) (3x²-4x-4)'/(3x²-7x-6)=lim(x→-2/3) (6x-4)/(6x-7)=-8/(-11)=8/11.
г) lim(x→-2) (4x-x³)/(2x²+3x-2)=(неопределённость 0/0)=
=lim(x→-2) (4x-x³)'/(2x²+3x-2)'=lim(x→-2) (4-3x²)/(4x+3)=-8/(-5)=1,6.